2019
DOI: 10.4103/ijmr.ijmr_1973_17
|View full text |Cite
|
Sign up to set email alerts
|

Statins & risk of Clostridium difficile infection

Abstract: Background & objectives:Clostridium difficile infection is one of the most common healthcare-associated infections worldwide. Recent epidemiologic studies have suggested that statin users may have a lower risk of C. difficile infection, although the results are inconsistent. This meta-analysis was conducted with the aim of summarizing all available data to assess the risk of C. difficile infection among statin users versus non-users.Methods:A literature review was performed using the MEDLINE and EMBASE databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Other than their cholesterol-lowering effect, they also have an anti-inflammatory and immunomodulatory properties [42]. According to a recent metaanalysis of available data, the risk of developing CDI was approximately 25% lower in statin users compared with non-users [43]. However, this meta-analysis included eight observational studies with significant heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Other than their cholesterol-lowering effect, they also have an anti-inflammatory and immunomodulatory properties [42]. According to a recent metaanalysis of available data, the risk of developing CDI was approximately 25% lower in statin users compared with non-users [43]. However, this meta-analysis included eight observational studies with significant heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Statins are cholesterol-lowering drugs and are widely used for the prevention of cardiovascular disease. Because of their anti-inflammatory, as well as their antimicrobial activity [4][5][6] along with additional evidence that statins may reduce neuro-inflammation and blood-brain barrier dysfunction [7][8][9], numerous clinical studies have assessed their impact on the outcome of many different infectious diseases [10][11][12][13][14][15][16][17]. However, although statins were reported to have beneficial effects in a murine model of Lyme borreliosis [18], we were unable to find any report on the impact of statins on the severity or course of Lyme borreliosis in humans.…”
Section: Introductionmentioning
confidence: 99%
“…42 The plausibility of these associations is uncertain, but small studies have previously demonstrated that HMG CoA reductase inhibitors are associated with lower risk of CDI through enhanced neutrophil function and lower risk of GIB through endothelial stabilization. 43 , 44 , 45 However, the identified protective association of several medications used to treat sequelae of metabolic syndrome also raises suspicion that the associations could be related to unmeasured confounding from increased healthcare utilization or unrecognized methodologic bias similar to the obesity paradox. 46 Despite this suspicion, in the case of CDI, it is difficult to construct a conceptual model that links medications that treat sequelae of metabolic syndrome and reduced exposure to traditional CDI risk factors, such as antibiotic use, hospitalization, and inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%